Use and evaluation of the Czech version of the SF-36 questionnaire self-reported health status of medical students - Skalská, H; Sobotík, Z; Jezberová, D; Mares, J (Central European journal of public health, 2000)
SF-36 questionnaires were completed by 231 medical students of the Faculty of Medicine in Hradec Králové (1997, 1998). Results of measurements of eight health dimensions are presented here. Significantly lower values for bodily pain were found in the group of overweight students. Students with some reported cured diseases have significantly lower values for bodily pain and general health dimensions in comparison with students without any reported disease. In our sample a high rate of non-smokers (86.4% men and 93.6% women) and low rate of students with BMI > 25 (18.4% men and 3.8% women) were found. About 30% of respondents reported one or more cured diseases. In addition to the SF-36 questionnaire, students in 1998 completed also a special one-page form (3). The one-page form enabled direct estimates of the eight dimensions of the health status on a scale from 0% to 100%. This study compares the results of measurement of the health status for both instruments. Differences found here are compared and discussed with similar comparisons in an American study (3). Results in both studies are similar but not the same. An indirect measurement of health status with specific questions in the SF-36 is more objective than a direct measurement with the one-page form. Nevertheless, the SF-36 is limited in the number of possible answers for some dimensions (RP, RE). In that case, our results indicate that a percentage scale from the one-page form seems better. Additionally this study compares the results of the SF-36 in Czech medical students with comparable samples from other three European countries. On average, the health dimensions of SF-36 in Czech medical students achieved the worst values in comparison with samples from Switzerland, Germany and Great Britain.
Keywords: studenti lékařství; Students, Medical; Male; Švýcarsko; Obesity; Health Surveys; United Kingdom; Česká republika; chronická nemoc; obezita; Adult; Pain; dospělí; činnosti denního života; mužské pohlaví; Chronic Disease; reprodukovatelnost výsledků; průzkumy a dotazníky; Reproducibility of Results; Smoking; Czech Republic; Germany; bolest; Health Status; lidé; ženské pohlaví; Humans; Switzerland; Body Mass Index; Německo; Spojené království; zdravotnické přehledy; zdravotní stav; Activities of Daily Living; index tělesné hmotnosti; Female; Surveys and Questionnaires; kouření